2017
DOI: 10.15226/jnhfs.2017.00194
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Alkaline Water in Hydrating Athletes

Abstract: to cause significant hypohydration and negatively affect shot precision and speed of reaction [2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
1
0
0
2
Order By: Relevance
“…The results obtained in our study are mostly confirmed in the available literature regarding the use of alkalized water, al-though few studies have been conducted on competitive athletes involved in intense anaerobic exercise [13,14,23] .…”
Section: Discussionsupporting
confidence: 85%
“…The results obtained in our study are mostly confirmed in the available literature regarding the use of alkalized water, al-though few studies have been conducted on competitive athletes involved in intense anaerobic exercise [13,14,23] .…”
Section: Discussionsupporting
confidence: 85%
“…Sampel dikategorikan menjadi 2 kelompok (eksperimen dan kontrol) dengan jumlah tiap kelompok sebanyak 20 sampel menggunakan teknik ordinal pairing berdasarkan data tes daya tahan kardiorespiraasi (VO2max) yang dilaksanakan satu bulan sebelum pelaksanaan penelitian oleh peneliti dengan metode YYIR1. Kelompok Eksperimen diberikan cairan alkali dengan pH-9 sebanyak 1800 ml, sedangkan kelompok kontrol diberikan minuman non-alkali (air mineral dengan pH-7) sebanyak 1800 ml (Kurylas, Zajac, Zydek, & Zajac, 2017). Metode Pemberian minuman alkali maupun non-alkali menggunakan planned drinks dimana dibagi menjadi 3 waktu pembagian.…”
Section: Metodeunclassified
“…Hasil diatas menjelaskan pengaruh signifikan konsumsi alkali pH-9 terhadap kadar laktat dan denyut nadi istirahat, pH-9 dapat memperlambat pembentukan asam laktat dan mempercepat proses denyut nadi pemulihan. Teori lain juga menjelaskan pemberian cairan yang tepat dapat mencegah penurunan performa pada atlet selama latihan maupun bertanding (Kurylas, Zajac, Zydek, & Zajac, 2017).…”
Section: Pembahasanunclassified